Relationship between internal communications and Management of Public Controversy - Elías Villanueva, Enrique (2015)
The main objective of our research is to understand how internal communication relates to the management of public controversy in employees of a municipality located in Lima. In the research process we established the relationship between message handling and decoding of employees, as well as the relationship between source credibility and empathy generated in the internal public. Finally, we determined the relationship between the bidirectional communication and mutual understanding among the partners. To develop this study we have chosen the non-experimental design, applicative research is correlational and descriptive level; it has developed inductive, deductive, analytical and statistical method. The population consists of 45 units of analysis, employees of a municipality of Lima. For its part, the sample consisted of 30 units of analysis.